Wielopoziomowe relacje między literaturą religijną Tatarów Wielkiego Księstwa Litewskiego a przekładami Biblii na języki narodowe - Kulwicka-Kamińska, Joanna (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2019)
The article presents the genesis and the features of the Renaissance religious writings of the Tatars of the Grand Duchy of Lithuania in the context of the translations of the Bible into national languages. An analysis was performed on a Tatar tefsir, which – according to the most recent research – is a translation of the Qur’an into a European language – the third translation of this kind in the world. Due to the fact that in the 16th century a Polish and even a European Qur’anic translational tradition did not exist, this translation makes reference to the Biblical-psalter literature of the Middle Ages and to the translations of the Scripture of the Reformation, inter alia as far as the selection of the methods and the ways of translation or the adoption of specific translational solutions is concerned. Thus the translation belongs to the translational tradition of sacred books and to the most important trends of Polish and European culture. In this context, a medieval tradition (a continuation of the achievements of translation studies of the 15th c.) and the innovation of the Renaissance overlap. There is an analogy with the 16th-century Biblical printed texts, which also represent a transitional stage – they make reference to a medieval tradition and they also take advantage of the benefits of humanist Biblical studies.